STRATEGI INTEGRASI SOSIAL WILAYAH PENGEMBANGAN IBU KOTA NEGARA BERBASIS MULTIKULTURAL DI PENAJAM PASER UTARA, KALIMANTAN TIMUR (STUDI KASUS: DESA WONOSARI, KECAMATAN SEPAKU, KABUPATEN PENAJAM PASER UTARA) - Irhamni Rahman,; Alfan Ramdoni, (Journal of Innovation Research and Knowledge, 2025)
The relocation of the National Capital (IKN) from Jakarta to Penajam Paser Utara (PPU), East Kalimantan, presents new challenges regarding social integration in a multicultural region. This study aims to identify the aspects involved in the social integration process in Wonosari Village, Sepaku District, and to analyze effective strategies for promoting social integration in the area. The methodology employed is a qualitative approach using a case study, which involves in-depth interviews and field observations. The research findings indicate that high ethnic and cultural diversity, effective multicultural communication, and inclusive public policies are important aspects in creating social harmony. This study recommends the development of inter-ethnic dialogue initiatives, cross-cultural communication training, and participatory policies to support sustainable social integration in the IKN. These findings are expected to serve as a reference for the development of social integration strategies in other regions with similar characteristics.